2011
DOI: 10.1590/s1807-59322011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for early treatment discontinuation in patients with obsessive-compulsive disorder

Abstract: INTRODUCTION:In obsessive-compulsive disorder, early treatment discontinuation can hamper the effectiveness of first-line treatments.OBJECTIVE:This study aimed to investigate the clinical correlates of early treatment discontinuation among obsessive-compulsive disorder patients.METHODS:A group of patients who stopped taking selective serotonin reuptake inhibitors (SSRIs) or stopped participating in cognitive behavioral therapy before completion of the first twelve weeks (total n = 41; n = 16 for cognitive beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…SAD is also mentioned as a predictor of worse response to both pharmacotherapy and psychotherapy for OCD in a sample that overlaps with ours (Belotto-Silva et al, 2012) and as a factor associated with early treatment abandonment (Diniz et al, 2011a). In a recent study by Kelly et al (Kelly et al, 2012), patients with comorbid BDD and SAD showed greater functional impairment than the BDD only and SAD only groups.…”
Section: Discussionmentioning
confidence: 99%
“…SAD is also mentioned as a predictor of worse response to both pharmacotherapy and psychotherapy for OCD in a sample that overlaps with ours (Belotto-Silva et al, 2012) and as a factor associated with early treatment abandonment (Diniz et al, 2011a). In a recent study by Kelly et al (Kelly et al, 2012), patients with comorbid BDD and SAD showed greater functional impairment than the BDD only and SAD only groups.…”
Section: Discussionmentioning
confidence: 99%
“…They also observed better outcomes, in terms of compliance, with an increased frequency of consultations in the initial phase of their study. 106 …”
Section: Treatment Of Refractory Obsessive-compulsive Disordermentioning
confidence: 99%
“…Regarding the chance of abandonment of pharmacological treatment, comorbid major depression has been decribed to diminish the chance of abandonment [17]. While another study has shown that comorbid agoraphobia, social phobia, generalized anxiety disorder and somatization disorder increase the chance of abandonment [18].…”
mentioning
confidence: 99%
“…Regarding pharmacological intervention, there is some evidence that reducing the length of intervals between medical appointments (seeing patients every 2 weeks instead of every month) might be helpful to prevent early treatment abandonment [18]. Likewise, as OCD patients with comorbid generalized anxiety and somatization disorder are more prone to abandon treatment due to medications' side effects, it might be helpful to assign these patients to psychotherapy whenever possible and to carefully choose drugs with better side-effect profiles for each specific patient [18]. There is also evidence that selective SRIs are associated with better treatment adherence than clomipramine due to the side-effect profile of the later [22].…”
mentioning
confidence: 99%